Graphane electrochemistry : electron transfer at hydrogenated graphenes - Poh, Hwee Ling (2013)
Graphane, the hydrogenated derivate of graphene is a highly novel material in the field of two dimensional nanocarbon related research. Preparation of hydrogenated graphene is achieved via a high-pressure/high-temperature (up to 150 bar and 500 °C) thermal exfoliation procedure of graphite oxide. We investigated the properties of the materials via voltammetry and electrochemical impedance spectroscopy to establish the electron transfer rates of hydrogenated graphenes to compare against non-hydrogenated graphene. Understanding the electrochemistry of graphane is crucial towards the exploration of the materials for future practical applications.